If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8n + 4) + -1(n + (-2)) = 0 Reorder the terms: (4 + 8n) + -1(n + (-2)) = 0 Remove parenthesis around (4 + 8n) 4 + 8n + -1(n + (-2)) = 0 4 + 8n + -1(n + -2) = 0 Reorder the terms: 4 + 8n + -1(-2 + n) = 0 4 + 8n + (-2 * -1 + n * -1) = 0 4 + 8n + (2 + -1n) = 0 Reorder the terms: 4 + 2 + 8n + -1n = 0 Combine like terms: 4 + 2 = 6 6 + 8n + -1n = 0 Combine like terms: 8n + -1n = 7n 6 + 7n = 0 Solving 6 + 7n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 7n = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 7n = 0 + -6 7n = 0 + -6 Combine like terms: 0 + -6 = -6 7n = -6 Divide each side by '7'. n = -0.8571428571 Simplifying n = -0.8571428571
| 5m+4m-28=45 | | 24-4x=15x | | b-36.9=5.1b | | 3m+1=4-6 | | -16(-19+11r)-18= | | -(6+5r)=-6-5r | | 635-35= | | (9n+1)-(6n+(-2))= | | d-182=-5d-8 | | (-3n+1)-(-5n+8)= | | A=x^2-3x+2 | | 5x+4(9x+4)=32 | | -20p+16=-9p-18-13p | | 3x^7+3x-15=0 | | 9-ln(5-x)=0 | | x^2-8x+16=-2 | | 6+2p-4=7p+11-4p | | -2x-14=6 | | 9+11a=-5a+12 | | (3n+1)-(5n+(-7))= | | n+137=-2n-4 | | 4d-5=0 | | 4y+(y+35)=180 | | p(x)=(x-(2-3i))(x-(2+3i)) | | 0=12x^2-40x-32 | | (-7n+(-3))-(-9n+5)= | | 18m-14=18m+18+2m | | -6+4=14y-10-13y | | 25/5(2+3)=25 | | 8n-9=n+285 | | (-9n+4)-(-2n+(-5))= | | 2abs(x-15)+abs(15-x)=27 |